Long-term outcome of lower extremity bypass surgery in patients with chronic kidney disease and critical limb ischemia in Germany - Meyer, Philipp; Surmann, Johanna; Epple, Jasmin; Böckler, Dittmar; Schmitz-Rixen, Thomas; Grundmann, Reinhart T. (Annals of vascular surgery, 2024)
Background - The aim of this study is to present short- and long-term outcomes after lower extremity bypass (LEB) surgery in patients with chronic limb-threatening ischemia and chronic kidney disease (CKD), differentiated by peripheral artery disease (PAD) Fontaine stage III and IV. - Methods - Retrospective analysis of anonymized data from a nationwide German health insurance company (AOK). Data from 22,633 patients (14,523 men) who underwent LEB from 2010 to 2015 were analyzed, presenting 18,271 with CKD stage 1/2, 2,483 patients with CKD stage 3, and 1,879 with CKD stage 4/5. - Results - Perioperative mortality (60-day mortality) was 7.2% for CKD stage 1/2, 12.4% for CKD stage 3, and 19.8% for CKD stage 4/5. Patients with PAD stage IV had significantly higher perioperative mortality (10.3%) than patients with PAD stage III (4.5%). The perioperative major amputation rate depended significantly on PAD stage IV (odds ratio [OR]: 2.57 confidence interval [CI]: 2.16-3.05, P < 0.001), the LEB level below the knee and crural/pedal (OR: 2.49 CI: 2.14-2.90, P < 0.001), CKD stage 4/5 (OR: 1.28, CI: 1.06-1.54, P = 0.009), and the presence of diabetes mellitus type 2 (OR: 1.19, CI: 1.05-1.36, P = 0.007). Kaplan-Meier estimated long-term survival of up to 9 years after surgery was 31.7% for patients with CKD stage 1 and 2, 14.3% for CKD stage 3, and only 10.1% for CKD stage 4 and 5 (P < 0.001). PAD Fontaine stage IV versus III (hazard ratio: 1.64, CI: 1.56-1.71, P < 0.001), but not bypass level, had an independent adverse influence on long-term survival. - Conclusion - CKD and PAD stage were equally significant independent predictors of patient survival and major adverse cardiovascular events with higher PAD and CKD stages associated with less favorable long-term outcomes.